The impact of bilateral brachial-ankle pulse wave velocity difference on cardiovascular disease and all-cause mortality - Zheng, Mengyi; Zhang, Xinyuan; Zhao, Quanhui; Chen, Shuohua; Guo, Xinying; Wang, Chi; Jonas, Jost B.; Wu, Shouling; Guo, Caixia (Frontiers in Cardiovascular Medicine, 2023)
Background This study aims to investigate the association between an elevated bilateral pulse wave velocity difference (BPWVD) and cardiovascular diseases (CVDs) and all-cause mortality. Methods This study included a total of 38,356 participants. A multivariable Cox proportional hazards regression was used to assess the association between high BPWVD and the increased risk of CVDs and all-cause mortality by calculating hazard ratios (HRs) with 95% confidence intervals. Results A total of 1,213 cases of CVDs were identified over a mean duration of 6.19 years, including 886 cases of cerebral infarction (CI), 105 cases of intracerebral hemorrhage (ICH), and 222 cases of myocardial infarction (MI), along with 1,182 cases of all-cause mortality. The median BPWVD was 42 cm/s (19–80 cm/s). After adjusting for all confounders and baseline brachial-ankle PWV (baPWV), our analysis revealed a significant correlation between a higher risk of CVDs, MI, and all-cause mortality with an increase in BPWVD per standard deviation. HRs (95% confidence interval) were found to be 1.06 (1.01–1.11), 1.11 (1.02–1.21), and 1.07 (1.04–1.10), respectively. Among the participants with higher baPWV on the left side, the HRs (95% confidence interval) were 1.08 (1.02–1.14) for CVDs, 1.27 (1.10–1.46) for incident ICH, 1.16 (1.00–1.24) for incident MI, and 1.10 (1.07–1.15) for all-cause mortality, for per standard deviation increase in BPWVD. Conclusions Our findings reveal a significant correlation between elevated BPWVD and the risks of developing CVDs and all-cause mortality. This highlights the importance of thoroughly evaluating BPWVD as a means of detecting individuals at risk for CVDs and mortality.